2009 11th Electronics Packaging Technology Conference 2009
DOI: 10.1109/eptc.2009.5416559
|View full text |Cite
|
Sign up to set email alerts
|

The effect of driving waveforms on droplet formation in a piezoelectric inkjet nozzle

Abstract: In the present study, double waveforms to drive a piezoelectric inkjet nozzle have been applied to the droplet formation of low viscosity liquid. The effect of the driving voltage and time separation between the pulses was observed. Even though several satellites are produced in the single waveform, the droplet formation could be precisely controlled in the double waveform. The shorter is the time separation, the smaller droplet is formed. The main effect of double waveform is that the second pulse reduces the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The performance of the droplet ejection process can be characterized by responses such as the droplet velocity, volume, consistency, shape and directionality. These parameters are affected by factors such as the fluid properties, nozzle geometry and waveform design (Kwon, 2009, 2010; Shin and Sung, 2009; Gan et al , 2009; Liou et al , 2010; Wijshoff, 2010; Tekin et al , 2008). The effects of these factors have been the subject of many experimental (Dong et al , 2006a, b) and computational studies (Bogy and Talke, 1984; Xu and Basaran, 2007).…”
Section: Principles Of Inkjet Printingmentioning
confidence: 99%
“…The performance of the droplet ejection process can be characterized by responses such as the droplet velocity, volume, consistency, shape and directionality. These parameters are affected by factors such as the fluid properties, nozzle geometry and waveform design (Kwon, 2009, 2010; Shin and Sung, 2009; Gan et al , 2009; Liou et al , 2010; Wijshoff, 2010; Tekin et al , 2008). The effects of these factors have been the subject of many experimental (Dong et al , 2006a, b) and computational studies (Bogy and Talke, 1984; Xu and Basaran, 2007).…”
Section: Principles Of Inkjet Printingmentioning
confidence: 99%
“…The key to success in this regard was an adaptation of the pulse shape of the piezoelectric signal. In detail, compared to the conventionally employed pulse shape, the initial voltage was drastically reduced to 5 V while the amplitude was increased to approximately 25 V. Shin et al previously proposed a double-trapezoid waveform to reduce satellite formation for low-viscosity inks . By altering the break time between the two pulses, the liquid momentum is reduced and thus satellite formation is suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, compared to the conventionally employed pulse shape, the initial voltage was drastically reduced to 5 V while the amplitude was increased to approximately 25 V. Shin et al previously proposed a double-trapezoid waveform to reduce satellite formation for low-viscosity inks. 66 By altering the break time between the two pulses, the liquid momentum is reduced and thus satellite formation is suppressed. The short single spike in the used pulse shape is supposed to have the same effect, counteracting the satellite-forming Rayleigh instability often visible for low-viscosity liquids.…”
Section: ■ Discussionmentioning
confidence: 99%
“…However, during droplet generation, many satellite droplets were produced, leading to a wide size distribution of the droplets. Shin et al [ 23 ] also reported that, for low viscosity liquid, satellites were generated when a single-pulse waveform was applied, whereas when a double-pulse waveform was utilized, the satellites were eliminated. A simple change in the time separation can precisely control the droplet size.…”
Section: Introductionmentioning
confidence: 99%